Peran Peran Pendidikan Akidah dan Akhlak Dalam Membentuk Karakter Peserta Didik - ulhaq, nida (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
Faith and morals education has a very important role in shaping the character of students. Through this education, it is hoped that students can develop strong moral and spiritual values, and be able to face life's challenges wisely. This research aims to analyze the contribution of faith and morals education in forming students' character. With a qualitative approach, data was obtained through literature studies and interviews with several teachers and educators. The research results show that faith and morals education can increase students' understanding of religious values, form positive attitudes, and strengthen their personal integrity in everyday life.